2017
DOI: 10.1073/pnas.1620673114
|View full text |Cite
|
Sign up to set email alerts
|

Human and rat gut microbiome composition is maintained following sleep restriction

Abstract: Insufficient sleep increasingly characterizes modern society, contributing to a host of serious medical problems. Loss of sleep is associated with metabolic diseases such as obesity and diabetes, cardiovascular disorders, and neurological and cognitive impairments. Shifts in gut microbiome composition have also been associated with the same pathologies; therefore, we hypothesized that sleep restriction may perturb the gut microbiome to contribute to a disease state. In this study, we examined the fecal microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
104
5
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(127 citation statements)
references
References 48 publications
11
104
5
7
Order By: Relevance
“…It is of note that a study published by Zhang et al [17] used a similar sleep restriction protocol (20h/day sleep disruption using a rotating bar for 7 days) but found no changes in the fecal microbiome. There are a few potential reasons for this discrepancy.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is of note that a study published by Zhang et al [17] used a similar sleep restriction protocol (20h/day sleep disruption using a rotating bar for 7 days) but found no changes in the fecal microbiome. There are a few potential reasons for this discrepancy.…”
Section: Discussionmentioning
confidence: 92%
“…This has led to the hypothesis that there is a relationship between inadequate sleep and the gut microbiome. Only a small number of studies have tested this hypothesis, using heterogeneous sleep disruption protocols (e.g., acute sleep restriction [14,15], chronic sleep fragmentation [16]), in humans [14,17], mice [15,16], and rats [17], and have yielded mixed results [17]. More research is therefore required to explore the relationship between sleep, the gut microbiome, and potential mediators of microbe-host interactions.…”
mentioning
confidence: 99%
“…The Dietary Approaches to Stop Hypertension (DASH) diet is one of the interventions used to reduce blood pressure (98). This diet is rich in fruits and vegetables, as well as low-fat dairy, and at the same time has a low content of saturated and total fat (105).…”
Section: Restoring the Balance: Current And Potential Interventionsmentioning
confidence: 99%
“…The interaction between microbiome and sleep/sleep deprivation has already been studied in both humans and animal models. In 2 human partial sleep deprivation studies (sleep restricted to 4 hours per night across 2‐5 days), one found slight changes in microbial phyla, while in the other study, no changes in the operational taxonomic units (describing the richness of the phyla) were found . A study in elderly humans associated sleep quality and cognitive function with differences in gut microbiome .…”
Section: New Playersmentioning
confidence: 99%
“…A study in elderly humans associated sleep quality and cognitive function with differences in gut microbiome . Sleep fragmentation for 2 weeks in mice resulted in transitions between gut microbiota phyla, while sleep restriction for 20 days in rats resulted in small decrease in operational taxonomic units . The studies suffer from low number of analysed subjects, indicating the preliminary nature of these findings.…”
Section: New Playersmentioning
confidence: 99%